PENGARUH STRUKTUR MODAL TERHADAP SHU KOPERASI: ANALISIS PERBANDINGAN ANTARA MODAL SENDIRI DAN MODAL PINJAMAN: THE EFFECT OF CAPITAL STRUCTURE ON COOPERATIVE RESULTS: COMPARATIVE ANALYSIS BETWEEN OWN CAPITAL AND LOAN CAPITAL - Kalsum, Ummi; Beliwati, Kosim; Randy, Hidayat; Arraditya, Permana (Jurnal Aplikasi Manajemen dan Bisnis, 2024)
This study aims to analyze the influence of capital structure on Residual Operating Results (SHU) on the primary Army cooperatives in Palembang City, focusing on the comparison between own capital and borrowed capital. The data used in this study includes total own capital, total loan capital, and SHU from 11 primary Army cooperatives in Palembang City for the 2021-2023 period. The analysis method used is multiple linear regression to test the relationship and influence of each type of capital on SHU. The results of the study show that own capital and loan capital have a significant influence on Cooperative SHU. Capital itself has a significant effect on the Cooperative SHU, while loan capital does not have a significant influence on the Cooperative SHU. Capital itself tends to have a greater positive impact on the increase in SHU than borrowed capital. These findings indicate that cooperatives that are more dependent on their own capital tend to have more stable and optimal financial performance in producing SHU. This study suggests that cooperative managers consider the composition of a balanced capital structure by prioritizing their own capital to minimize financial risks and improve business sustainability. This study provides insights for cooperatives in determining more effective financial strategies to improve the welfare of their members.